Sistem Pendukung Keputusan Pemilihan Jaksa Terbaik dengan Menerapkan Metode MABAC (Studi Kasus: Kejaksaan Negeri Medan) - Bagus Nur Ihwa; Natalia Silalahi; Rivalri Kristianto Hondro (Journal of Computer System and Informatics (JoSYC), 2020)
The selection of the Medan District Attorney as part of the Attorney General's Office of the Republic of Indonesia carried out several mutations of the chief prosecutor who were taken by manually calculating performance scores. The criteria taken in the evaluation are orientation, service, integrity, commitment, discipline, and cooperation aspects require a decision support system (SPK) to accelerate and facilitate decision making. Decision support systems are used to help decision making in an organization to facilitate decision making. Where no one knows for sure how decisions should be made. One of the methods used in this decision support system is MABAC. Decision support system to assist local governments in the selection of the best prosecutors in accordance with specified conditions and criteria. The MABAC method is one of a set of decision support system methods that are included in the multi criteria decision making method (MABAC) group